Anti-Inflammatory Activity of Marine Sponge Aaptos sp. to the Plasma Interleukin-1β Level in Wistar Male Rats - Adryan Fristiyohadi; Wahyuni Wahyuni; Wa OIL. Kalimin; La OMJ. Permana; Saripuddin Saripuddin; Idin Sahidin (Universitas Padjadjaran, Indonesia)
Inflammation is the response of the body to injury and infection characterized by swelling, heat, pain, and redness. This study aimed to investigate the anti-inflammatory effect of Aaptos sp. ethanolic extract to plasma interleukin (IL)-1β level of Wistar male rats. Aaptos sp. was macerated with 96% ethanol for 3 x 24 hours. Inflammation was induced with administration of 1% carrageenan intraplantarly. Animals were divided into 5 treatment groups, i.e., positive control (diclofenac sodium 3598 ppm); Aaptos sp extract 50 ppm; Aaptos sp extract 100 ppm Aaptos sp extract 200 ppm; and negative control (0.5% Na CMC). After 1 hour, blood was collected and assayed using enzyme-linked immunosorbent assay (ELISA) kit. The results showed that plasma IL-1β levels of animals were decreased by Aaptos sp ethanolic extract. The administration of 50 ppm of extract showed no significant difference (p>0.05) in IL-1β level in first and second hour measurement, but indicated a statistically significant decrease after three hour (p<0.05). The administration of 100 ppm of extract showed no significant difference (p>0.05) in every hour. Significant reduction was observed in the administration of 200 ppm of extract, but the elevation of IL-1β levels was also observed at third hour measurement. In conclusion, ethanolic extract of Aaptos sp. had anti-inflammatory activity and its effective dose was 50 ppm.